Kegiatan Sosial dan Komunitas Membentuk Generasi Cinta Al-Qur’an Sejak Dini - Annisa Nur Shafira; Mismiwati (CV. Doki Course and Training, 2025)
This article discusses social and community activities aimed at fostering a love for the Qur'an from an early age. These activities include memorizing Qur'anic verses, prayers, hadiths, as well as teaching Qur'anic recitation, tajweed, and interpretation through madrasahs and tilawati groups. Collaboration among village governments, religious leaders, and the community is key to successfully cultivating children's and teenagers' interest in reading and understanding the Qur'an. This program not only enhances skills in reading and memorizing the Qur'an but also builds strong Islamic character and love for Islamic culture. The positive impacts include increased religious awareness, enthusiasm for reading the Qur'an, and the formation of independent, morally upright young generations.